Heterogeneous Catalysis and Parahydrogen‐Induced Polarization - Pokochueva, Ekaterina V.; Burueva, Dudari B.; Salnikov, Oleg G.; Koptyug, Igor V. (Chemphyschem, 2021)
Parahydrogen‐induced polarization with heterogeneous catalysts (HET‐PHIP) has been a subject of extensive research in the last decade since its first observation in 2007. While NMR signal enhancements obtained with such catalysts are currently below those achieved with transition metal complexes in homogeneous hydrogenations in solution, this relatively new field demonstrates major prospects for a broad range of advanced fundamental and practical applications, from providing catalyst‐free hyperpolarized fluids for biomedical magnetic resonance imaging (MRI) to exploring mechanisms of industrially important heterogeneous catalytic processes. This review covers the evolution of the heterogeneous catalysts used for PHIP observation, from metal complexes immobilized on solid supports to bulk metals and single‐atom catalysts and discusses the general visions for maximizing the obtained NMR signal enhancements using HET‐PHIP. Various practical applications of HET‐PHIP, both for catalytic studies and for potential production of hyperpolarized contrast agents for MRI, are described. Catalysts for parahydrogen‐induced polarization: Heterogeneous parahydrogen‐induced polarization (HET‐PHIP) is a hyperpolarization technique based on the pairwise addition of hydrogen atoms from parahydrogen molecules to unsaturated substrates over heterogeneous catalysts. In this review we follow HET‐PHIP development from the first observation reported in 2007 to the latest advances and discuss its possible applications in the fields of catalytic research and biomedicine.